P16INK4a Deletion Ameliorates Damage of Intestinal Epithelial Barrier and Microbial Dysbiosis in a Stress-Induced Premature Senescence Model of Bmi-1 Deficiency - Zhou, Jiawen; Hou, Chenxing; Chen, Haiyun; Qin, Ziyue; Miao, Zi’an; Zhao, Jingyu; Wang, Qiuyi; Cui, Min; Xie, Chunfeng; Wang, Rong; Li, Qing; Zuo, Guoping; et al. (Frontiers in Cell and Developmental Biology, 2021)
This study aimed to determine whether Bmi-1 deficiency leads to intestinal epithelial barrier destruction and microbiota dysfunction, which members of the microbial community alter barrier function with age, and whether p16INK4a deletion could reverse the damage of intestinal epithelial barrier and microbial dysbiosis. Intestines from Bmi-1–deficient (Bmi-1–/–), Bmi-1 and p16INK4a double-knockout (Bmi-1–/–p16INK4a–/–), and wild-type mice were observed for aging and inflammation. Duolink Proximity Ligation Assay, immunoprecipitation, and construction of p16INK4a overexpressed adenovirus and the overexpressed plasmids of full-length, mutant, or truncated fragments for occludin were used for analyzing the interaction between p16INK4a and occludin. High-throughput sequencing of V4 region amplicon of 16S ribosomal RNA was conducted using intestinal microbiota. We found Bmi-1 deficiency destructed barrier structure, barrier function, and tight junction (TJ) in intestinal epithelium; decreased the TJ proteins; increased tumor necrosis factor α (TNF-α)–dependent barrier permeability; and up-regulated proinflammatory level of macrophages induced by intestinal microbial dysbiosis. The transplantation of fecal microbiota from wild-type mice ameliorated TJ in intestinal epithelium of Bmi-1–/– and Bmi-1–/–p16INK4a–/– mice. Harmful bacteria including Desulfovibrio, Helicobacter, and Oscillibacter were at a higher level in Bmi-1–/– mice. More harmful bacteria Desulfovibrio entered the epithelium and promoted macrophages-secreted TNF-α and caused TNF-α–dependent barrier permeability and aging. Accumulated p16INK4a combined with occludin at the 1st–160th residue in cytoplasm of intestinal epithelium cells from Bmi-1–/– mice, which blocked formation of TJ and the repair of intestinal epithelium barrier. P16INK4a deletion could maintain barrier function and microbiota balance in Bmi-1–/– mice through strengthening formation of TJ and decreasing macrophages-secreted TNF-α induced by Desulfovibrio entering the intestinal epithelium. Thus, Bmi-1 maintained intestinal TJ, epithelial barrier function, and microbiota balance through preventing senescence characterized by p16INK4a accumulation. The clearance of p16INK4a-positive cells in aging intestinal epithelium would be a new method for maintaining barrier function and microbiota balance. The residues 1–160 of occludin could be a novel therapeutic target for identifying small molecular antagonistic peptides to prevent the combination of p16INK4a with occludin for protecting TJ.